2022
DOI: 10.1177/23259671221089984
|View full text |Cite
|
Sign up to set email alerts
|

Return to Sport for Professional and Subelite Ice Hockey Players After Arthroscopic Surgery for Femoroacetabular Impingement Syndrome

Abstract: Background: Femoroacetabular impingement syndrome (FAIS) is a common cause of hip pain, which can prevent ice hockey players from sports participation. Hip arthroscopy is often performed to relieve pain and enable the player to return to sport (RTS) and return to performance (RTP). Purpose: To determine the RTS and RTP rates for ice hockey players at the professional and subelite levels after hip arthroscopy for FAIS. Study Design: Case series; Level of evidence, 4. Methods: High-level ice hockey players who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Since there, in team sports, might be a natural variation in the number of games played during one season, regardless of injury or not, a lower level than 100% was set for the definition of RTP. The variation was calculated from the variation in games played in a random set of players, without known medical history, from the highest league in Sweden the seasons of 2020 and 2021, a method previously described when evaluating RTS and RTP in ice hockey players [ 15 ]. In this current study it was found there could be a variation of 20% in games played between seasons, therefore, the limit for RTP was set at 80%.…”
Section: Methodsmentioning
confidence: 99%
“…Since there, in team sports, might be a natural variation in the number of games played during one season, regardless of injury or not, a lower level than 100% was set for the definition of RTP. The variation was calculated from the variation in games played in a random set of players, without known medical history, from the highest league in Sweden the seasons of 2020 and 2021, a method previously described when evaluating RTS and RTP in ice hockey players [ 15 ]. In this current study it was found there could be a variation of 20% in games played between seasons, therefore, the limit for RTP was set at 80%.…”
Section: Methodsmentioning
confidence: 99%
“…Periacetabular osteotomy, the standard treatment for hip dysplasia, which reorients the acetabular osseous coverage for good short-and longterm outcomes [8], is not applicable for BHD, given the invasiveness of the procedure and the associated risk of complications [42]. In recent decades, hip arthroscopy has been an effective treatment option with good outcomes for many hip pathologies [26]; however, its applicability for hip dysplasia is still in dispute due to its reported failure rate and the potential of exacerbating the instability, subsequently resulting in osteoarthritis [29,36]. Recently, with a better understanding of preoperative predictors and capsule management, surgeons have achieved significantly improved clinical outcomes for a select group of patients with BHD who have undergone hip arthroscopy [1,14,25].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Nonetheless, on-going hip and groin pain can have debilitating long-term effects, such as increased depen-dency on medication, higher surgical intervention rates, and potentially early retirement. [7][8][9] While hockey athletes can still participate in training and competition, their performance capacity is likely to be reduced. 1,3 This diminished performance capacity can negatively impact their ability to showcase their skills to coaches and scouts, which may limit playing time and reduce their chances of being selected for higher competitive levels.…”
Section: Introductionmentioning
confidence: 99%